ON-LINE PROFESSIONAL TRAINING FOR WORKERS WITH THE MOODLE SYSTEM TO IMPROVE PROFESSIONAL SKILLS IN GREEN CONSTRUCTIONS - Lazov, Lyubomir; Teirumnieka, Erika; Teirumnieks, Edmunds; Atanasova, Nedka; Karadzhov, Tsanko (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
On the global agenda, environmental issues are becoming ever more pressing every moment. At present, it is not enough for individual countries to tackle global climate issues on their own. The time has come for a joint effort to mitigate climate change. The Paris Agreement is an agreement within the United Nations Framework Convention on Climate Change, dealing with greenhouse-gas-emissions mitigation, adaptation, and finance, starting in the year 2020. The Paris Agreement's long-term goal is to keep the increase in global average temperature to well below 2 °C above pre-industrial levels, and to limit the increase to 1.5 °C, since this would substantially reduce the risks and effects of climate change. It is not enough for states to sign this type of act, they need to take active steps to implement them and achieve the set goals. Energy, green construction, resource saving, educating the population, new and advanced teaching methods - all that is required for any global setup to be locally addressed. Now, we are in a situation where the exchange of transnational experience and knowledge is an important stage in solving energy efficiency issues through the education prism. This article will provide an analysis of the experience of four countries in the field of green construction.